Development of a Socio-Scientific Issues-Based Electronic Learner Activity Sheets to Enhance Learners’ Critical Thinking Skills on the Topic of Hydrocarbons - Wanda Hanna Sajida; Rusly Hidayah; Angela Shrestha (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
The transformation of the 21st century necessitates that educational institutions produce learners with essential competencies, particularly critical thinking skills (CTS). Learners’ CTS in hydrocarbon topics remain at a relatively low level. Development of these skills is achievable through the presentation of controversial socio-scientific issues in society as stimuli for training structured critical thinking processes. This research aims to determine the feasibility of socio-scientific issues (SSI)-based electronic learner activity sheets (E-LAPD) in enhancing learners' CTS. The study employed the 4D model, executed up to the develop stage. A field trial of the E-LAPD was conducted with 36 learners from class XI-2 at SMAN 20 Surabaya. The research instruments included pretest and post-test sheets for CTS and cognitive domains, as well as review, validation, observation, and learner response questionnaires. The developed E-LAPD was declared feasible based on a median score of 5 categorized as 'highly valid.' Learners’ responses reached 91.67%, further supported by s learners’ activity observations reached 95.56%. The E-LAPD proved effective, as evidenced by a p-value (sig.) of 0.000 in the t-test, indicating that post-test scores significantly outperformed pretest scores. Additionally, the effectiveness of E-LAPD was confirmed by an N-gain score of 0.686, categorized as 'moderate'. further indicate that the SSI-based E-LAPD was effective in supporting the improvement of students’ CTS in hydrocarbon learning